Influence of clone and deletion size on outcome in chronic lymphocytic leukemia patients with an isolated deletion 13q in a population‐based analysis in British Columbia, Canada. Issue 1 (22nd September 2015) - Huang, Steven J. T.; Gillan, Tanya L.; Gerrie, Alina S.; Hrynchak, Monica; Karsan, Aly; Ramadan, Khaled; Smith, Adam C.; Toze, Cynthia L.; Bruyere, Helene
Abstract : Deletion of the long arm of chromosome 13 (del(13q)) as the sole abnormality in chronic lymphocytic leukemia (CLL) portends a good prognosis; however, there is great outcome heterogeneity within this subgroup. The percentage of cells with a del(13q) (clone size) and the extent of the deletion are two factors that may affect outcome in CLL patients with isolated del(13q). We analyzed 248 CLL patients from the BC Provincial CLL database identified as having isolated del(13q) detected pretreatment by interphase fluorescence in situ hybridization to determine what impact clone and deletion size had on overall survival (OS) and treatment free survival (TFS). Patients with 60% or more of nuclei with a del(13q) had shorter TFS and shorter OS. A large deletion, encompassing the RB1 gene locus, was detected in half of the 90 cases with available specimens for testing, and there was no significant difference in OS and TFS between RB1 ‐deleted and RB1 ‐not‐deleted cases. Further study in a larger sample size is required to determine the clinical interest of RB1 locus testing; however, clone size of del(13q) does predict TFS and OS and may better refine prognosis in this clinically heterogeneous population. © 2015 Wiley Periodicals, Inc.